Analysis of the Effect of Learning Models and Gender on Students’ Critical Thinking Skills - Adam Malik; Siti Zakiah Annasir Darajat; Rena Denya Agustin; Andi Rohendi Nugraha (STKIP Singkawang, 2023)
This study analyzes the implementation of the Interactive Lecture Demonstration (ILD) model and the influence of gender on critical thinking skills in momentum and impulse. This study used a quasi-experimental with a pretest-posttest control group design. The research instruments were observation sheets and critical thinking skills tests. The analysis data were calculating the percentage of activity on the observation sheet, N-Gain, and independent-sample t-test. The results showed that percentage of learning in the experimental class (ILD) for teacher activities was 76% and for students were 77% in a good category. The control class (demonstration) for teacher and student activity was 77% in a good category. The average N-Gain of the experimental class was 0.62 and the control class was 0.55 in the medium category. The t-test results showed that there were differences in the improvement of students' critical thinking skills in the experimental class and the control class. Besides, gender has no effect on students' critical thinking skills in the experimental class. Meanwhile, in the control class, gender affects students' critical thinking skills. Thus, the implementation of the ILD model can improve students' critical thinking skills. Gender does not affect students' critical thinking skills in the ILD model.